Design Optimization of Propellant Grain and Nozzle Contour to Improve Performance of Solid Rocket Propulsion - Muhammad Ihsan Abyan; Aang Nuryaman; Bagus Hayatul Jihad; Soleh Fajar Junjunan; Asmiati Asmiati (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
A rocket is a spacecraft, guided missile, or flying vehicle that boosted by a chemical reaction resulting from the combustion of propellant in the rocket motor. One of the essential parameters in the development of rocket motors is design optimization to improve the propulsion performance of the rocket. Increasing the propulsion performance of the rocket will increase the flight performance of the rocket, in terms of its maximum range or the altitude of the rocket trajectory. This study examined the determination of the design parameter values of a rocket motor by looking at it as an optimization problem with constraints. The problem studied was limited to the case of the second-stage rocket motor. A genetic algorithm was used to solve the resulting optimization problem of propellant grain configuration cases and a characteristic method for designing the bell nozzle. The results obtained indicated an increase in total impulse by 10% compared to the results before optimization.